FBN2 promotes the proliferation, mineralization, and differentiation of osteoblasts to accelerate fracture healing - Jian Huang; Jun Huang; Nan Li; Lanfang Wang; Quanhao Xiao (Scientific Reports)
Abstract Fracture is a disease in which the continuity of bone is interrupted or the integrity of bone is destroyed due to various reasons. It can be life-threatening when severe fractures occur. The RNA-seq datasets related to ‘fracture’ were screened and the common differentially expressed genes (DEGs) were determined. Protein-protein interaction network was constructed to identify hub genes. The fracture mice model was constructed and HE staining was performed to observe the histological characteristics of fracture. The expression of inflammatory factors and hub genes were evaluated by ELISA and qRT-PCR. CCK-8 assay, flow cytometry and Alizarin Red S staining were performed to evaluate the effects of fibrillin2(FBN2) on viability, apoptosis and mineralization of MC3T3E1 cells, respectively. Western blot was executed to measure expression of osteogenic markers (ALP and RUNX2). A total of 78 common DEGs were screened from GSE157460 and GSE152677 datasets. FBN2 was down-regulated in fracture and identified as the hub gene. In fracture mice, the thickness of the compact bone decreased in Day 1, accompanied by callus and woven bone formation, filled with a large number of osteoblasts, while IL-1β, IL-6 and TNF-α levels were increased. FBN2 enhanced cell viability and mineralization, suppresses apoptosis of MC3T3E1 cells, and facilitated the expression of ALP and RUNX2. Meanwhile, the knockdown of FBN2 demonstrated opposing trends. Through bioinformatics analysis, FBN2 was identified as the hub gene in fracture, and FBN2 promoted the proliferation, mineralization, and differentiation of osteoblasts, thereby accelerating fracture healing.